Epidemiology of Celiac Disease in Northern Morocco in 2018–2021: A Descriptive Cross-Sectional Study - Haddadi, Maroua; Mellouki, Ihsan; Benmakhlouf, Yousra; Diakite, Adama; Khaili, Aymane; Barrijal, Said; Essalmani, Haiat (UI Scholars Hub, 2023)
Celiac disease is an autoimmune disease caused by gluten. This retrospective cross-sectional study with descriptive and analytical aims was conducted over three years, from 2018 to 2021. The participants were 280 patients diagnosed with celiac disease registered in the Gluten Intolerant and Allergic Association of the North in the Tangier-Tetouan-Al Hoceima region. The prevalence and incidence of celiac disease in this region were 1/135 and 1/253, respectively. The average age was 21.18 ± 1.13, and the first symptoms appeared between 10 and 25 years. The data showed a female predominance of 68% versus 32% for males, with a male/female sex ratio of 0.45. The clinical signs of celiac disease manifested more in gastrointestinal symptoms. This study obtained data on 22.6% of microcytic hypochromic anemia patients and 40.7% of Helicobacter pylori infections. In addition to celiac disease, the patients showed other pathologies with different rates: repeated spontaneous abortions (2.14%), type 1 diabetes mellitus (1.42%), autism (1.42%), dermatitis herpetiformis (0.72%), cancer(0.72%), and epilepsy (0.35%). Serologically, anti-transglutaminase antibodies were positive in 47.2% of patients. Analyses of histological data from intestinal biopsies from 141 patients were positive in 50.8% of patients. There was a minor correlation between the serological profile and the degree of atrophy.